Functional graphene oxide for organic pollutants removal from wastewater a mini review - Kong, Qiaoping (Environmental technology, 2023)
Graphene oxide (GO), an important derivative of graphene, with a variety of active oxygen-containing groups (hydroxyl, carboxyl and epoxy) on its surface is easy to be functionalized to obtain adsorbent with high adsorption capacity. To date, the adsorption behaviour of organic pollutants by functionalized GO adsorbents have been extensively studied, but there has been no systematic review regarding the functionalization method of GO for the purpose to remove organic pollutants from wastewater. The leading objective of this review is to (i) summarize the functionalization strategies of GO for organic pollutants removal (covalent functionalization and non-covalent functionalization), (ii) evaluate the adsorption performance of functional GO towards organic pollutants by taking aromatic pollutants and dyes as examples and (iii) discuss the regeneration property and adsorption mechanism of functional GO adsorbent. In addition, the problems of existing studies and future research directions are also identified briefly